Revealing incentives for vertical integration in the presence of glocal policies - Pierpaolo Giannoccolo; Cecilia Vergari (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
Local and regional policy makers are acquiring an increasingly active role in affecting firms' specialization decisions that in turn influence firms' vertical organization. We analyse the relation between vertical integration incentives and trade liberalization in the presence of glocal policies, i.e., specific (local) policies that have international (global) impact. More precisely, one of the most important reasons for vertical integration in the presence of sunk costs of specialization is avoiding the risk of hold up. We introduce the idea that this sunk cost can be manipulated by the policy maker at national/regional/local level. We characterize the conditions under which policies are effective in achieving a particular equilibrium in terms of vertical structure and specialization decision. The main result is that the policy effectiveness is stronger the higher is the importance of the hold-up problem. In particular, we investigate how glocal policies interact with policies that affect the market openness (trade policy). We find that for high values of the specialization upgrade cost, trade policies are ineffective. At the same time, if the trading cost is very low, glocal policies are ineffective. Finally, in the presence of intermediate specialization upgrade and trading cost, either policy supplements the other policy.
Keywords: D23; F15; F23; H54; L22; 330